Airflow Study of A Closed Room in the Public Spaces and Mass Transportation for Healthy and Safe from The Transmission of Covid19 - Bagus Endar Bachtiar Nurhandoko; Rio K. Martha; Kaswandhi Triyoso; Satryo A. Wibowo; Sri Widowati (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2021)
We present engineering airflow to intercept the transmission of Covid19 in public spaces and public transportations, which relatively fast and simple. This technique is to suppress effectively and as massive as possible the spread of aerosols and droplets contaminated with the COVID-19 virus that is flying in the air by providing a vertical downward flow using fans placed on the ceilings and the use of floors of the certain material so that aerosol and microdroplets will not bounce back up, difficult to roll, and firmly attached to the floor. The numerical airflow simulation shows that positioning the fan on the ceiling of the room will cause the air particle to move faster downward, which will push the microdroplets to fall to the floor more quickly, so that the microdroplets and aerosols will quickly move away from the most risk organs from the transmission, namely the mouth and nose. The contactangle test results on several floor materials always show a value of fewer than 90 degrees. These phenomena cause microdroplets or aerosols that fall to the floor will stick tightly and not easily roll. This phenomenon will cause the room to be more sterile from aerosols and microdroplets that may be contaminated with Covid19. The room will be healthier and safer. This technique can be a solution that is relatively inexpensive and simple to implement on a field scale and is very effective in reducing the radius of the spread of droplets or aerosols in closed spaces, both public spaces and public transportation, such as trains and city buses which are very susceptible to Covid19 transmission.